Expression of mTOR in normal and pathological conditions - Marques-Ramos, Ana (2023)
The mechanistic/mammalian target of rapamycin (mTOR), a protein discovered in 1991, integrates a complex pathway with a key role in maintaining cellular homeostasis. By comprising two functionally distinct complexes, mTOR complex 1 (mTORC1) and mTORC2, it is a central cellular hub that integrates intra- and extracellular signals of energy, nutrient, and hormone availability, modulating the molecular responses to acquire a homeostatic state through the regulation of anabolic and catabolic processes. Accordingly, dysregulation of the mTOR pathway has been implicated in a variety of human diseases. While major advances have been made regarding the regulators and effectors of the mTOR signaling pathway, insights into the regulation of mTOR gene expression are beginning to emerge. Here, we present the currently available data regarding the mTOR expression regulation at the level of transcription, translation, and mRNA stability and systematize the current knowledge about the fluctuations of mTOR expression observed in several diseases, both cancerous and non-cancerous. In addition, we discuss whether mTOR expression changes can be used as a biomarker for diagnosis, disease progression, prognosis, and/or response to therapeutics. We believe that our study will contribute to the implementation of new disease biomarkers based on mTOR as it gives an exhaustive perspective on the regulation of mTOR gene expression in both normal and pathological conditions.